Gales - Stapleton, Barry, author.
1 online resource (xiii, 113 pages)
Keywords: "This title was first published in 2000. This volume tells the fascinating story of the origins, development, growth and survival of a small country brewery in Hampshire. Employing and analyzing a wealth of original documentation, it examines the local environment both before establishment of the brewery and during the 150 years of its existence. While the performance of Gales Brewery is examined in the context of the British brewing industry as a whole, the thread of family involvement is woven throughout the volume. The contribution of contrasting individual entrepreneurs is examined in absorbing detail, from the half century of domination by George Alexander Gale to the subsequent century of contribution by the Bowyer family. Gales is exceptional in being one of the very few family breweries to survive the mania of mergers and takeovers in the brewing industry. This very readable book will be of considerable interest to business, economic, family and local historians."--Provided by publisher.